2010
DOI: 10.1021/jf101715g
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Emptying and Short-Term Digestibility of Thermally Oxidized Sunflower Oil Used for Frying in Fasted and Nonfasted Rats

Abstract: Four-hour in vivo digestibility of sunflower oil used in frying was tested in fasted and nonfasted rats. For three consecutive days, 12 male Wistar rats received 1 g of unused oil (controls, C), while 12 received 1 g of used oil (test group, T). On the night of day 3, 6 rats from each group were fasted (FC, FT) while the other 6 animals from each group had free access to food (NFC, NFT). On day 4, FC and NFC received 2 g of unused oil, while FT and NFT received 2 g of used oil. Luminal gastric and intestinal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 32 publications
2
17
2
Order By: Relevance
“…Thus, linoleic acid hydroperoxides administered intragastrically was converted into hydroxyls, epoxyketones, hexanal and 9-oxononanoic acid, time-dependently (52,53) . Other authors have reported that gastrointestinal glutathione peroxidase plays an important role in the mucosal transport and in the conversion of hydroperoxides to more OH OH Lipase Márquez-Ruiz et al (18 -20) , Gonzá lez-Muñoz et al (21) and Olivero-David et al (22,23) Low lipolysis of TAG polymers Márquez-Ruiz et al (20) and González-Muñ oz et al (21) TAG polymers decrease lipolysis of non-modified TAG Márquez-Ruiz et al (20) and González-Muñ oz et al (21)…”
Section: Model Systems and Specific Oxidation Compoundsmentioning
confidence: 98%
“…Thus, linoleic acid hydroperoxides administered intragastrically was converted into hydroxyls, epoxyketones, hexanal and 9-oxononanoic acid, time-dependently (52,53) . Other authors have reported that gastrointestinal glutathione peroxidase plays an important role in the mucosal transport and in the conversion of hydroperoxides to more OH OH Lipase Márquez-Ruiz et al (18 -20) , Gonzá lez-Muñoz et al (21) and Olivero-David et al (22,23) Low lipolysis of TAG polymers Márquez-Ruiz et al (20) and González-Muñ oz et al (21) TAG polymers decrease lipolysis of non-modified TAG Márquez-Ruiz et al (20) and González-Muñ oz et al (21)…”
Section: Model Systems and Specific Oxidation Compoundsmentioning
confidence: 98%
“…Again, several different situations made this topic complex and difficult to study and clearly demand to avoid doing any generalization as iron content in meat is rather variables as we have discussed in Section 4 . In addition, the consumption of “red” meat is expected to induce more oxidation effects after a large interprandial period (e.g., 15 h) that after a shorter one (4–5 h) as the activity and expression of gastrointestinal antioxidant enzymes is highly modified by the fasting conditions [ 59 ].…”
Section: Meat Consumption As a Source Of Oxidative Stressmentioning
confidence: 99%
“…Recently, it was reported that, in Wistar rats, the digestibility of thermally treated sunflower oil is up to 30% lower than that of fresh sunflower oil. 88 It is still unclear whether the reduced bioavailability of frying oils derives from the poor absorption of polar oxidation products or whether those oxidation products affect the catalytic activity of pancreatic lipase. The digestibility of lipids may also be altered by heating as a consequence of the physical damage of the original food structure.…”
Section: Effect Of Heating On Lipid Digestibilitymentioning
confidence: 99%